Administrative Localism and Vertical Normative Conflict in the Riau Islands Regional Legal Aid Regulation - Pery Rehendra , Sucipta; Niken Febriani , Safitri (JURNAL KUASA, 2026)
This study examines political and policy conflicts in the implementation of regional legal aid regulations in Indonesia. Although legal aid is a constitutional right guaranteed equally to all citizens, Regional Regulation of Riau Islands Province Number 3 of 2017 (Perda Kepri 3/2017) imposes residency-based administrative requirements that potentially restrict access for non-local residents. The regulation reflects administrative localism, namely the use of regional autonomy and bureaucratic mechanisms to redefine access to constitutional rights and public services. This research employs normative legal methods using statutory, conceptual, and policy approaches. The analysis focuses on the normative structure of Perda Kepri 3/2017 and its compatibility with higher legal instruments governing legal aid, population administration, and public services. The findings show that administrative localism operates through three interconnected layers: definitional restrictions, substantive-procedural limitations, and institutional gatekeeping mechanisms. These arrangements create vertical normative conflicts with the Legal Aid Law, the Population Administration Law, Presidential Regulation No. 67 of 2011, and the Public Services Law. The regulation also reveals a broader political policy conflict between the principle of equal citizenship promoted by the central government and regional policy preferences emphasizing territorial and fiscal prioritization within Indonesia’s decentralized governance system. This study concludes that the issue is not merely juridical but also politics, as regional discretion has narrowed the implementation of universal constitutional rights. Accordingly, the study recommends a three-tier harmonization strategy consisting of vertical regulatory revision, horizontal inter-regional cooperation, and a rights-based reorientation of regional public service policies to ensure equal access to legal aid throughout Indonesia.